Transpormasi Madrasah dan Pesantren dalam Mengahadapi Perubahan Sosial di Era Digital - Mahyudin, Edy; Idi, Abdullah; Karoma, Karoma; Hasan, Muflikhul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the forms of transformation undertaken by madrasahs and pesantren in responding to social changes in the digital era. The research employs a library research method, examining ideas, theories, and previous research findings without conducting field data collection. Data sources are derived from academic books, journal articles, research reports, and policy documents related to Islamic education and digitalization. The research process involves identifying key issues, selecting relevant literature, and conducting content analysis to discover patterns and key findings. The data analysis technique in this literature review research uses content analysis by examining, interpreting, and synthesizing various written sources systematically to understand the transformation of madrasahs and pesantren in the digital era. The results indicate that madrasahs and pesantren play a fundamental role in instilling moral, ethical, and spiritual values through their distinctive Islamic educational traditions. However, in a modern context, pesantren have also evolved into agents of community empowerment through curriculum innovation, entrepreneurship training, and the strengthening of digital literacy to prepare adaptive generations. Although globalization presents challenges such as digital inequality and resistance to change, pesantren have managed to adapt by integrating technology into learning while maintaining their Islamic identity. Thus, madrasahs and pesantren are proven to be dynamic institutions that preserve tradition while being able to transform in accordance with the demands of the times.